Introducing English language : a resource book for students - Mullany, Louise; Stockwell, Peter (London: Routledge, 2015)
'Introducing English Language is the foundational book in the Routledge English Language Introductions series and gives comprehensive coverage of the essential aspects of the field, as well as providing an introduction to key disciplines of linguistics such as historical, social and psycholinguistics, and also core areas in language study including acquisition, standardisation and the globalisation of English. The new edition includes updated and revised exercises; extended further reading section; expanded coverage of morphology; new readings and a brand new companion website. This accessible textbook is an essential resource for all students of English language and linguistics'--
Includes bibliographical references and index.
Keywords: English language -- Grammar; English language